GMO’S - THE TRADE-OFFS BETWEEN ECONOMIC BENEFITS AND PERCEIVED HEALTH RISKS - Gheorghe, ORZAN; Alexandra, PRICOP G.; Madalina, MIHALACHE Maria (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 20 (2018): Annales Universitatis Apulensis Series Oeconomica, 2018)
Food safety has become an important topic in the last decades as pesticides, chemical additives, hormones and other technological processed substances began to raise awareness among consumers, organizations and governments. At international scale it is being noticed an increasing concern that genetically modified food might have an unforeseen impact on human health. On the other hand, biotechnology has the ability to eliminate worldwide hunger and malnutrition in an efficient matter. Indirect costs that are associated with the production and adoption of genetically modified food as well as the potential to protect and conserve the environment need to be taken into account in the cost, benefit and perceived risk analysis. This paper describes the trade-offs between possible risks associated with genetically modified organisms and the economic benefits.